PVA/polyethyleneimine-functionalized graphene composites with optimized properties. (5th June 2016) - Shao, Leishan; Li, Jingjing; Guang, Yu; Zhang, Yuliang; Zhang, Heng; Che, Xinyuan; Wang, Yinghan
Abstract: This study presents a straightforward route to fabricate robust poly(vinyl alcohol) (PVA)/polyethyleneimine-functionalized graphene (PVA/rGO/PEI) composite films by combining of surface modification, reduction and composite preparation. Branched polyethylenimine (PEI), as an effective reducing agent and surface modifier of graphene oxide (GO), has been presented to yield PEI-functionalized graphene in PVA aqueous solution. The obtained PVA/PEI-functionalized graphene composites exhibited significant improvements in strength and toughness. At a PEI: GO ratio of 0.5:1, the tensile strength and Young's modulus of PVA/rGO/0.5PEI composite increased by 55.8% and 43.1%, respectively from pure PVA, and the elongation at break also increased from 77.1% (for PVA/GO composite) to 147.3%. With regard to simultaneous strengthening and toughening effects, the strong interfacial interactions produced by the mechanism of hydrogen bonding between amine of PEI and hydroxyl groups of PVA play a key role, which not only increase load transfer efficiency but accelerate crystallization of PVA. Graphical abstract: Highlights: A facile one-pot strategy was proposed to fabricate PVA/functionalized graphene composites. GO was simultaneously functionalized and reduced by PEI in PVA aqueous solution. Strong interfacial interactions were built between PEI-functionalized graphene and PVA. PEI-functionalized graphene/PVA composites exhibited greatly improvements in strength and toughness.